The effects of team composition on the performance of public healthcare workers in Malaysia / Azlyn Ahmad Zawawi and Aizzat Mohd Nasurdin - Ahmad Zawawi, Azlyn; Mohd. Nasurdin, Mohd Nasurdin (UiTM Cawangan Kedah, 2022)
Healthcare workers are the pulse of medical services in the country. In medical teams, the composition of workers plays a big impact in the delivery of healthcare services. In this paper, team composition consists of team diversity and team skills. The effects of team composition on the performance of healthcare workers are analyzed and discussed. This study involved 300 healthcare teams in Malaysia. The paper intends to examine the relationship between team diversity and team skills on the team performance of healthcare workers. Team performance is characterized by team task performance and team contextual performance. Data were analyzed using the structural equation modeling (SEM) technique and results indicated that team diversity has no significant effect on team performance (team task performance β = 0.081, p>0.05; team contextual performance β=0.026, p>0.05). Meanwhile, team skills have proven to have a significant effect on both dimensions of team performance (task performance β = 0.1446, p<0.01; and team contextual performance β = 0.1149, p<0.05). Furthermore, a fit model was explored between all the factors. This study would assist in the understanding of team composition and team performance among healthcare workers in Malaysia.